The effect of Nitrofurantoin on liver on Albino mice (Baghdad Science Journal, 2025)
the current study Included, evaluation the impact of Nitrofurantoin drug on liver in albino mice, 128 male albino mice have been used . Animals treared with (150,200 Mg/Kg) for 8 weeks . NFI caused histological changes in liver represented by , swelling of hepatocytes, disappearance of radial arrangement , vaculation of liver cells , increasing of kupffer cells and appearance of giant cells. NFT caused Congestion of blood vessels and infiltration of inflammatory cells in liver in all used concentrations.